EFL students’ strategies in answering the listening section of the Longman TOEFL - Tengku Maya Silviyanti; Rahayu Ramadhani; Iskandar Abdul Samad (Studies in English Language and Education, 2020)
This study investigated the EFL students’ strategies in answering the Listening section of the Paper-based TOEFL test. The samples of this research were purposively selected consisting of 30 English major students at Universitas Syiah Kuala, Banda Aceh, Indonesia. The samples were selected based on their recent TOEFL scores. All the selected samples achieved low TOEFL scores, especially for the Listening section. The data were gained by means of closed questionnaire and interviews. The interviews were conducted with three students of the 30 students and they were selected randomly. The results of the questionnaire revealed that the top three strategies the students used when answering the TOEFL questions ranged from the strategies of (1) ‘before listening, I tried to anticipate the topic by looking at the answer in the test book’, (2) ‘while listening, I tried to determine the topic or main idea for each conversation, and (3) ‘before listening, I tried to anticipate what the questions would be and I listened specifically for the answer’. This imply that a majority of students used strategies only to answer part B (dialogues) and part C (monologues) of the TOEFL Listening section. These parts were considered more difficult since many students were not familiar with the topics. Meanwhile, strategies for part A were neglected. These students often forgot to choose answers in this section. Unfortunately, strategies for part A are also important because they can achieve higher scores if the 30 questions in this part are answered correctly.